Risks of seismic activities on built environment in Nigeria. (9th July 2019) - Akpabot, Akpabot I.; Ede, Anthony N.; Olofinnade, Oluwarotimi M.; Bamigboye, Gideon O.
Buildings are designed to be safe to prevent collapse caused by natural or man-made factors. Until recently, Nigeria was believed to be aseismic due to its distance from earthquake zones. However, recent seismic activities have led to the prediction of possible future earthquake occurrence in Nigeria. This study estimates the impact of seismic hazard on the built environment in Nigeria. A model is created to estimates the number of casualties and built areas that would be affected by earthquake of different ground motions. Monte Carlo simulation is used to derive random data of building area, occupancy limits, construction quality (CQ) and failure probability (Pf) for the computational analysis. The results showed that an average seismic intensity measure will affect between 1, 000-1, 060 km 2 of building area and about 6.5-6.9 million people will be affected. Consequently, these huge losses require urgent mitigating efforts to reduce risks of damages when earthquake occur.